Intrinsic normalizations of semi-non-holonomic hypercomplexs SNGr(1, n, 2n-3) in the projective space Pn - Navickis, Kazimieras (Lietuvos matematikos rinkinys, 1998)
In this paper the problem of intrinsic normalizations of a semi-non-holonomic hypercomplexes SNGr(1, n, 2n-3) in n-dimensional projective space Pn is considered. It is proved that there exists three kinds of the intrinsic normalizations of SNGr(1, n, 2n-3). So called intrinsic normal spaces of the first and the second kind, some correspondences betwen the normal spaces are obtained. The geometrical interpretations of all these objects and correspondences are given.